PENGGUNAAN HAK INTERPELASI DEWAN PERWAKILAN RAKYAT PERSPEKTIF FIQIH SIYASAH - SHOBAHAH, NURUSH S. (IAIN Tulungagung, 2017)
The House of Representative in the Indonesian constitution constitutes the main state institution which holds the legislative function together with other state legislative institutions. In addition, the House of Representative also has a supervisory function. In carrying out the oversight function, the House of Representative has the right of interpellation, the right of inquiry, and the right to express opinion. In practice, the use of the right of interpellation often generates conflict between the House of Representative and the government. In this article, the author tried to assess the monitoring instrument of the House of Representativeâs interpellation from the perspective of siyasah jurisprudence because, basically, Islam as a true religion has offered the basic concept which provides the benefit of ideal life to the politics.Keywords: Hak Interpelasi, Dewan Perwakilan Rakyat, Fiqih Siyasah